A Commonly Used Biocide 2-N-octyl-4-isothiazolin-3-oneInduces Blood–Brain Barrier Dysfunction via Cellular Thiol Modification and Mitochondrial Damage - Kim, Donghyun (Int J Mol Sci, 2021)
Isothiazolinone (IT) biocides are potent antibacterial substances commonly used as preservatives or disinfectants, and 2-n-Octyl-4-isothiazolin-3-one (OIT; octhilinone) is a common IT biocide that is present in leather products, glue, paints, and cleaning products. Although humans are exposed to OIT through personal and industrial use, the potentially deleterious effects of OIT on human health are still unknown. To investigate the effects of OIT on the vascular system, which is continuously exposed to xenobiotics through systemic circulation, we treated brain endothelial cells with OIT. OIT treatment significantly activated caspase-3-mediated apoptosis and reduced the bioenergetic function of mitochondria in a bEnd.3 cell-based in vitro blood–brain barrier (BBB) model. Interestingly, OIT significantly altered the thiol redox status, as evidenced by reduced glutathione levels and protein S-nitrosylation. The endothelial barrier function of bEnd.3 cells was significantly impaired by OIT treatment. OIT affected mitochondrial dynamics through mitophagy and altered mitochondrial morphology in bEnd.3 cells. N-acetyl cysteine significantly reversed the effects of OIT on the metabolic capacity and endothelial function of bEnd.3 cells. Taken together, we demonstrated that the alteration of the thiol redox status and mitochondrial damage contributed to OIT-induced BBB dysfunction, and we hope that our findings will improve our understanding of the potential hazardous health effects of IT biocides.